Innovation Performance Growth Among Small And Medium Sized Firms In Malaysia: A Pilot Study - Rashidah, Mohamad Ibrahim; Wan Abd Aziz, Wan Mohd Amin; Abraham, Abasiti Victor (2017)
Innovation is seen as a means that aids in promoting opportunities for new businesses to grow in the market. It has been proven to have a significant increase in SMEs as well an expansion of business due to implementation of innovation. Hence, SMEs are in competition among themselves in Malaysia even throughout the world, to improve their strategic innovation in order for them to boost productivity as well sustain their performance growth. Thus, the purpose of this paper is to study/examine innovation performance growth among small and medium sized firms in Malaysia. Data collection was from 60 respondents from SMEs in the construction, service and manufacturing sectors that aid in determining the reliability and normality of data generated for this pilot survey analysis. SPSS version 23 was used in the analyzation of the data. The findings confirmed that the survey instruments used were reliable. The findings as well enlighten small and medium sized firms as well as policy makers that innovation is an essential tool in the present day business doings. Further studies should examine how small and medium sized firms can make a choice from a range of possibilities for innovation sources before they carry out the real innovation.